Réponses

2013-06-12T21:53:47+02:00

Bonsoir

 

A

4x +5y = 8

2x +2y = 3

 

tu élimines les x en multipliant la 2ème équation par -2

 

tu as

4x + 5y = 8

-4x -4y = -6

y = 2

 

4x+ 5y = 8

4x +10 = 8

4x = 8-10

4x = -2

x = -2/4 = -1/2

 

 

B

2x -3y = -5

5x -6y = 8

 

-4x +6y = 10

5x -6y = 8

x = 2

 

5x -6y = 8

10 -6y = 8

-6y = 8-10

-6y = -2

y = 2/6 ou 1/3

 

 

 

2013-06-12T22:05:28+02:00
Tu t'es trompe pour la b c'est
B
2x-3y=-5
5x-6y=-8
-4x+6y=10
5x-6y=-8
X=2

5(2)-6y=-8
10-6y=-8
-6y=-10-8
-6y=-18
Y=3